PEMBERIAN KOLOSTRUM PADA BAYI BARU LAHIR: PERSPEKTIF PARITAS DAN DUKUNGAN KELUARGA - Rahakbauw, Grenny Zovianny; Sulistiyowati, Dwi; Sidabutar, Rasmina Anggi Permatasari; Arifin, Hasriany; Ayu, Yennyka Dwi (Ensiklopedia of Journal, 2024)
Psychosocial development of school-age children are adaptive child has a motivation to learn, started to doing homework and active and playing with their friends. School-age children in Kapujan have a problem where the psychosocial development of the survey in March 2016 of 10 school-age children (6-12 years), by conducting interviews. Obtained, 6 children have lost their parents in the next 1-4 years ago with 4 children haven’t with psychosocial development. Somestimes, deviate behavior is difficult to learn, decreased school achievement and be subdued children. While the 4 children who did not experience the loss of a parent. 3 of them psychosocial normal. The goal of researchers is to look at the relationship have lost their parents to the psychosocial development of children in Kenagarian kapujan 2016, this study uses the method description correlative approach crosscektional and instrument tool used a questionnaire with a student population of 33 persons were made in the sample using techniques pourposive sampling "as a sampling technique Chi-Square results of this study with 33 respondents get, more than half of respondents had lost their parents were divorced as much as 54.5% in Kenagarian kapujan 2016 more than half of the respondents have an adaptive psychosocial development of as many as 66 , 7% in Kenagarian kapujan 2016, the results of research in getting the value of p = 0.047 (p